Mortality and morbidity in different immunization protocols for experimental autoimmune myocarditis in rats. (24th February 2014) - Schmerler, P.; Jeuthe, S.; O h‐Ici, D.; Wassilew, K.; Lauer, D.; Kaschina, E.; Kintscher, U.; Müller, S.; Muench, F.; Kuehne, T.; Berger, F.; Unger, T.; et al.
Abstract Aim We aimed to investigate the histological and clinical presentations of experimental autoimmune myocarditis (EAM) induced by different immunization schemes. Methods Male young Lewis rats were divided into five groups immunized by porcine myocardial myosin: subcutaneously (SC) 2 mg (in two 1‐mg doses on day 0 and 7), 0 mg (sham group) subcutaneously into rear footpads (RF), 0.25 mg RF, 0.5 mg RF or 1 mg RF (all RF once on day 0). On day 21, left ventricular (LV) function was assessed by cardiac magnetic resonance imaging and cardiac catheterization. The type and degree of myocardial inflammatory infiltrates were determined by conventional histology and immunohistochemistry. Results In the SC immunized rats and in the RF sham group, we observed 0% mortality, while in the actively RF immunized rats, mortality was 20, 20 and 44% for the 0.25 mg, 0.5 mg and 1 mg myosin doses respectively. Morbidity as defined by inflammatory infiltrates on haematoxylin and eosin (HE) staining was 22% in the SC immunized rats, 0% in the RF sham group and 100% in all actively RF immunized groups. We observed augmented relative ventricle weight and spleen weight, increased LV end‐diastolic pressure, reduced LV developed pressure and reduced LV ejection fraction in all with myosin‐immunized RF groups without any systematic dose effect. Conclusion Subcutaneous immunization to the neck and flanks did not induce a reproducible EAM, while RF myosin administration reliably led to EAM. Lower myosin doses seem to induce the complete histological and clinical picture of EAM while being associated with lower mortality, non‐specific symptoms and animal distress.